The Sugar Plantation in India and Indonesia : industrial production, 1770-2010 - Bosma, Ulbe, 1962- (New York, NY : Cambridge University Press, 2013)
'European markets almost exclusively relied on Caribbean sugar produced by slave labor until abolitionist campaigns began around 1800. Thereafter, importing Asian sugar and transferring plantation production to Asia became a serious option for the Western world. In this book, Ulbe Bosma details how the British and Dutch introduced the sugar plantation model in Asia and refashioned it over time. Although initial attempts by British planters in India failed, the Dutch colonial administration was far more successful in Java, where it introduced in 1830 a system of forced cultivation that tied local peasant production to industrial manufacturing. A century later, India adopted the Java model in combination with farmers' cooperatives rather than employing coercive measures. Cooperatives did not prevent industrial sugar production from exploiting small farmers and cane cutters, however, and Bosma finds that much of modern sugar production in Asia resembles the abuses of labor by the old plantation systems of the Caribbean'--
Includes bibliographical references (pages 285-311) and index.
Keywords: Sugar plantations -- India -- History; Sugar plantations -- Indonesia -- Java -- History; Sugar trade -- India -- History; Sugar trade -- Indonesia -- Java -- History